Pendampingan Senam Sehat dalam Rangka Meningkatkan Kebugaran Jasmani Lansia di Desa Mlaran - Rahma Wulan Intan Nuraini; Wissda Az Zahro Chairunnisa; Fitri Maulin Ni’mah; Ahmad Fatnan Ali; Teguh Nugroho; Salis Irvan Fuadi (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasing elderly population requires strategic community-based efforts to maintain physical fitness and quality of life among older adults. One of the main problems faced by elderly residents in Mlaran Village is the lack of regular physical activity, which leads to decreased physical fitness and functional capacity. This community service program aimed to improve elderly physical fitness through healthy exercise assistance based on community organizing. The program employed a participatory approach by actively involving elderly participants, community health volunteers, and village officials throughout the planning, implementation, and evaluation stages. The activities were conducted over three months, with exercise sessions held twice a week. The results showed an increase in elderly participation from approximately 60% to 85%, a reduction in minor physical complaints, and positive behavioral changes as elderly participants began engaging in independent physical activities. In addition, a community-based elderly exercise group was established as a new social institution, and local leaders emerged from among health volunteers to sustain the program. The assistance process also fostered collective awareness regarding the importance of physical activity as part of a healthy lifestyle. In conclusion, community-based healthy exercise assistance is effective in improving elderly physical fitness while promoting social transformation toward an active, healthy, and independent elderly community.